Presentation and communication skills in the academic preparation of students of pedagogy - A. Koleva; D. Branekova; Hr. Zafirov (Trakia Journal of Sciences)
The renewal of the educational system and the realization of innovative approaches are aimed at the formation of creative people, who develop, communicate and grow in the conditions of many dimensions and changing societies simultaneously adapting to a constantly changing and challenging environment. Integrating various communication channels into network spaces implies development of skills and competences not currently prioritized in the education system. ICT technologies, in combination with modern educational strategies, form a new tool for the realization of various learning objectives as well as effective means and methods of training adequate to the natural course of “digitalization” of the society as knowledge of digital technologies has become compulsory rather than optional. The universal nature of digital technologies facilitates the acquisition of other key competences related to different areas of knowledge, such as the acquisition of native or foreign languages. The goal of this study is to develop and introduce a practical model of forming presentation and communication skills based on ICT integration and language education of students who will become pedagogues.